A retrospective real-world study of the current treatment pathways for myelofibrosis in the United Kingdom: the REALISM UK study. (March 2022) - Mead, Adam J.; Butt, Nauman M.; Nagi, Waseem; Whiteway, Alastair; Kirkpatrick, Suriya; Rinaldi, Ciro; Roughley, Catherine; Ackroyd, Sam; Ewing, Joanne; Neelakantan, Pratap; Garg, Mamta; Tucker, David; et al.
Background: Myelofibrosis (MF) is a blood cancer associated with splenomegaly, blood count abnormalities, reduced life expectancy and high prevalence of disease-associated symptoms. Current treatment options for MF are diverse, with limited data on management strategies in real-world practice in the United Kingdom. Methods: The REALISM UK study was a multi-center, retrospective, non-interventional study, which documented the early management of patients with MF. The primary endpoint was the time from diagnosis to active treatment. Discussion: Two hundred patients were included (63% [ n = 126/200] with primary MF; 37% [ n = 74/200] with secondary MF). Symptoms and prognostic scores at diagnosis were poorly documented, with infrequent use of patient reported outcome measures. 'Watch and wait' was the first management strategy for 53.5% ( n = 107/200) of patients, while the most commonly used active treatments were hydroxycarbamide and ruxolitinib. Only 5% of patients proceeded to allogeneic transplant. The median (IQR) time to first active treatment was 46 days (0–350); patients with higher risk disease were prescribed active treatment sooner. Conclusion: These results provide insight into real-world clinical practice for patients with MF in the United Kingdom. Despite the known high prevalence of disease-associated symptoms in MF, symptoms were poorly documented. Most patients were initially observed or received hydroxycarbamide, and ruxolitinib was used as first-line management strategy in only a minority of patients. Plain Language Summary: Background: Myelofibrosis is a rare blood cancer associated with symptoms that can seriously affect a patient's daily life, such as enlarged spleen and decreased white and red blood cells. Although several treatments are available for patients with myelofibrosis, it is not clear which ones clinicians use most frequently. Methods: We aimed to review which treatments are usually given to patients with myelofibrosis in the UK, by collecting information from the medical records of 200 patients with myelofibrosis treated in different centres across the UK. Results: The results showed that the symptoms patients experienced were not always written down in the medical records. Similarly, clinical scores based on patient characteristics (which clinicians use to try to predict if a patient will respond to treatment well or not) were also missing from the medical records. Clinicians also rarely asked patients to complete questionnaires that try to measure the impact of myelofibrosis and its treatment on their health. The most common approach for patients with myelofibrosis in the UK was 'watch and wait', which over half of patients received. The most common drugs used for treatment were hydroxycarbamide and ruxolitinib; only a very small proportion of patients received a bone marrow transplant. On average, patients waited for 46 days before receiving a treatment, although patients considered to have a more aggressive type of disease received treatment sooner. Conclusion: The results of this study suggest that medical records can be missing key information, which is needed to decide which is the best way to treat a patient with myelofibrosis. They also suggest that clinicians in the UK prefer observation to treatment for a large number of patients with myelofibrosis. This could mean that the approach used for many patients with myelofibrosis does not help them to control symptoms that have an impact on their daily lives.